Density of states, optical and thermoelectric properties of perovskite vanadium fluorides Na₃VF₆ - Ali Hussain, Reshak, Prof. Dr. (Elsevier/NORTH-HOLLAND, 2014)
Link to publisher's homepage at http://www.journals.elsevier.com